Ответ:
x1 = - 8 \\ x2 = 1 \\ - 8 \leqslant x \leqslant 1" alt=" - {x}^{2} - 7x + 8 \geqslant 0 \\ {x}^{2} + 7x - 8 \leqslant 0 \\ x1 + x2 = - 7 \\ x1 \times x2 = - 8 = > x1 = - 8 \\ x2 = 1 \\ - 8 \leqslant x \leqslant 1" align="absmiddle" class="latex-formula">
![x + 3 \geqslant 0 \\ x \geqslant - 3 x + 3 \geqslant 0 \\ x \geqslant - 3](https://tex.z-dn.net/?f=x%20%2B%203%20%5Cgeqslant%200%20%5C%5C%20x%20%5Cgeqslant%20%20-%203)
объединим
![- 3 \leqslant x \leqslant 1 - 3 \leqslant x \leqslant 1](https://tex.z-dn.net/?f=%20-%203%20%5Cleqslant%20x%20%5Cleqslant%201)
-3; -2; -1; 0; 1
5 чисел